ANALISIS BIAYA OPERASIONAL UNTUK MENILAI KINERJA KEUANGAN PADA PT. BANK PEMBANGUNAN DAERAH SUMATERA UTARA - Siagian, Supriadi (Jurnal Mahkota Bisnis (Makbis), 2023)
This study aims to determine the effect of operations on financial performance based on Return on Asset (ROA) PT. Bank Pembangunan Daerah Sumatera Utara. In this study, there are several variables, namely operational costs consisting of sales costs (X1) administrative and general costs (X2), and financial performance based on ROA (Y). The research method used is descriptive quantitative analysis method. The sample in this research is financial statement data, income statement data, and operational budget which is obtained from PT. Bank Pembangunan Daerah Sumatera Utara from 2017 to 2019. The type of data used in this study is secondary data, the technique and data used are documentation. From the research results it is known that the operation has an effect on the operating profit obtained by PT. Bank Pembangunan Daerah Sumatera Utara, due to operational costs incurred by PT. Bank Pembangunan Daerah Sumatera Utara has fluctuated, causing the financial performance of PT. Bank Pembangunan Daerah Sumatera Utara also experienced fluctuations. It is known that NPM, TATO and ROA also fluctuate every year. Thus, to overcome this, the company management must be able to make the right and planned decisions in controlling costs so that the company's problems can be resolved